METTL3-YTHDF1 axis drives BCL-3 m6A methylation to promote the ferroptosis of brain microvascular endothelial cells during intracerebral hemorrhage - Hao Yin; Zhongying Ran; Tao Luo; Zexin Jin; Ying Tan; Jun Ma (Brain Research Bulletin)
Intracerebral hemorrhage (ICH) significantly impacts human health, with emerging evidence indicating that N6-methyladenosine (m6A) modifications serve a critical regulatory function in ischemic stroke. However, the underlying mechanisms remain largely unexplored. This study sought to comprehensively analyze aberrant m6A modification and its mechanistic implications following ICH. Differential expression of BCL-3 between Sprague-Dawley rat ICH models and control rats was identified through analysis of methylated RNA Immunoprecipitation and RNA sequencing data, revealing a close association with methyltransferase-like 3 (METTL3), an m6A methyltransferase. METTL3 knockdown and overexpression were conducted in an in vitro ICH model to further elucidate the roles of METTL3 and BCL-3 in apoptosis and ferroptosis. The results indicated that METTL3 knockdown significantly reduced BCL-3 expression, inhibited reactive oxygen species production, and decreased apoptosis and ferroptosis. Conversely, METTL3 overexpression resulted in the opposite effects. BCL-3 overexpression mitigated the effects induced by METTL3 knockdown. Moreover, YTHDF1 knockdown resulted in outcomes comparable to those observed following METTL3 knockdown. In vivo experiments demonstrated that METTL3 knockdown inhibited ferroptosis and protected brain tissue, whereas BCL-3 overexpression exacerbated brain damage. In conclusion, our findings suggest that BCL-3 expression, regulated by METTL3- and YTHDF1-mediated methylation, promotes apoptosis and ferroptosis following ICH, thereby contributing to neuronal injury. This study reveals a novel epitranscriptomic regulatory pathway involved in ICH pathology and identifies the METTL3-YTHDF1-BCL-3 axis as a promising therapeutic target for mitigating neuronal damage post-ICH.